PENGALAMAN BELAJAR MAHASISWA KEDOKTERAN DALAM PENGGUNAAN REKAMAN KULIAH SEBAGAI MEDIA PEMBELAJARAN - Lukman Hakim; Fundhy Sinar Ikrar Prihatanto; Musofa Rusli (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2019)
Background: Recorded lecture is a type of learning media which the lecturers record their voices when lecturing. This type of media is popular in many universities outside Indonesia. Faculty of Medicine Universitas Airlangga is developing electronic learning using recorded lecture in 2016. This study aimed to learn the experience of college student about the usage of recorded lecture, the impact to their learning style, and their hopes about the implementation of recorded lecture in Faculty of Medicine Universitas Airlangga. Method: This qualitative study applied content analysis design. The variable used are age, gender, intelligence quotient, learning style, learning equipment, experience when using learning media, and busyness in student affairs. Results: Eleven subjects are interviewed. The results are variably different between the subject. There are seven themes arise from the analysis results, for instance: 1) classical class alone was not enough, need another alternative; 2) the recorded lecture was similar with the one in internet; 3) used recorded lecture just for a few times; 4) recorded lecture was very beneficial; 5) the recorded lecture was too long; 6) college students are very busy outside the class; 7) a wish for the improvement og the recorded lectures, both quality and quality. Conclusion: The experience felt by medical education students on the use of recordings still varies. In general, students feel helped by the recording of lectures, on the other hand there are students who are not satisfied with the quality and quantity of lecture recordings provided by the campus. Massive and comprehensive improvements are needed in all aspects of providing lecture records, both in terms of teachers and in terms of technology support Keywords: recorded lecture, content analysis, qualitative research, medical student, electronic learning.